Silene crassiuscula (Caryophyllaceae), a new species from Sicily - Brullo, Salvatore; Brullo, Cristian; Cambria, Salvatore; Bacchetta, Gianluigi; Giusso Del Galdo, Gianpietro; Ilardi, Vincenzo (Phytotaxa, 2015)
Silene crassiuscula,, a new species of S. sect. Dipterosperma, is described and illustrated from North-Western Sicily. It is an annual halophyte with succulent growing on carbonatic or calcarenitic rocks of coastal stands. From the morphological point of view , S. crassiuscula appears to be similar to the species belonging to the S. colorata group especially to S. nummica, from Sardinia, from which it differs in several features chiefly regarding the habit, leaves, inflorescences, floral pieces and seed micro-morphology. An analytical key of the taxa belonging to this section is also provided.